ANALISIS MODEL BISNIS DAN TANTANGAN OPERASIONAL KOPI GEROBAK DI KOTA PALU - Citra Lestari; Siti Anisah; Adinda Prameswary Putry; Suasa Suasa; Dandan Haryono; Nurhayati Hamid (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
Street coffee sales, also known as coffee carts, are part of the city's informal economy that offers affordable coffee and independent business opportunities for small enterprises. However, they often face regulations and market pressures. This study was conducted to analyze the business models and operational challenges faced by street coffee sellers in Palu City. Through qualitative research, including in-depth interviews and observations, the study found that the business model of coffee cart vendors in Palu is highly dependent on flexible locations, competitive prices, and emotional relationships with customers. Some challenges include extreme weather, location permits, and competitive prices.